Evaluasi Retak Pada Slab Beton Lantai Kendaraan Gedung Parkir dan Metode Perbaikannya - Sulardi Sulardi (Media Ilmiah Teknik Sipil, 2018)
The aim to be achieved from this research activity is to provide an overview of the factors and causes of cracks, labar and crack depth on the concrete slab of the vehicle floor of the parking building and recommendations for improvement methods. This research method is a used research method and is a success story of crack evaluation and handling methods that have been carried out. The results showed that the crack width that occurred was 0.624-1.022 mm vs. 0.33 mm, out of tolerance. The results of the deflection measurements also show an average deflection in the concrete slab of the vehicle floor is 5.8-10.5 Cm and indicates that the crack has reached the concrete reinforcement, out of tolerance. With the results of this study, it is recommended that improvements be made with crack injection methods using low-pressure injection tools and specifications of an epoxy resin material.